Korelasi Antara Kadar Total Flavonoid dan Fenolik dari Ekstrak dan Fraksi Daun Jati Putih (Gmelina Arborea Roxb.) Terhadap Aktivitas Antioksidan: Correlation Between Total Phenolic and Flavonoid Contents of Jati Putih (Gmelina arborea Roxb.) Leaves Extract and Fraction Toward Antioxidant Activity - Nur, Syamsu; Sami, Fitriyanti Jumaetri; Awaluddin, Akbar; Afsari, Mutiara Indah Ayu (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
This experiment aims to determine the correlation of total phenolic and flavonoid content of jati putih leaves fraction (Gmelina arborea Roxb.) towards Antioxidant activity . Sample was extracted by maceration method using ethanol 70% to obtain the ethanol extract (EE), followed by liquid-liquid extraction method to obtain fraction of ethyl acetate (EA) and n-Hexane (EH). The phytochemical screening and determination of total phenolic and flavonoid content were done by colorimetric method. Antioxidant activity were done by DPPH, FRAP and ABTS methods. Phytochemical screening showed positive results for flavonoids, phenolic and saponins. The largest total phenolic content was found on EA (11,59 µg/ml ± 0,3 %b/b EAG) and the largest total flavonoid content was on EA (3,88 µg/ml ± 0,02 %b/b EK). The total phenolic and flavonoid content of Jati putih leaves has a correlation with antioxidant activity. The coefficient correlation of activity on reducingDPPH radical was 56,7% (total of phenolic content) and 57,8% (total of flavonoid content) and on iron reduction power in FRAP method was 99,9% (total of phenolics and flavonoids content). The relationship with the activity in reducing radical ABTS obtained coefficient correlation of 57,0% and 58,1% for total phenolic and flavonoids contents, respectively.